2018
DOI: 10.1007/s10047-017-1013-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on outcomes in patients undergoing implantation of continuous-flow left ventricular assist devices

Abstract: The purpose of this study was to analyze the effect of obesity on outcomes after continuous-flow left ventricular assist device (CF-LVAD) implantation. A single-center retrospective analysis was performed on 526 chronic heart failure patients who were implanted with the HeartMate II CF-LVAD (n = 403) or HeartWare HVAD (n = 123) between November 2003 and March 2016. Patients were stratified into 4 groups based on BMI: underweight (< 18.5 kg/m, n = 18, 3.4%), normal-weight (18.5-25 kg/m, n = 173, 32.9%), overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The increasing incidence and prevalence of obesity is accompanied by life‐limiting comorbidities including the metabolic syndrome, pulmonary hypertension, hypercoagulable state, atherosclerotic disease, arrhythmias, and HF. Our work confirms the results of several recent studies, which failed to detect a significant difference in short‐term and intermediate postoperative survival between obese and nonobese LVAD recipients . However, higher rates of hospital readmissions and complications such as AKI , infection , thromboembolism , and PT are often present in the obese cohort.…”
Section: Discussionsupporting
confidence: 90%
“…The increasing incidence and prevalence of obesity is accompanied by life‐limiting comorbidities including the metabolic syndrome, pulmonary hypertension, hypercoagulable state, atherosclerotic disease, arrhythmias, and HF. Our work confirms the results of several recent studies, which failed to detect a significant difference in short‐term and intermediate postoperative survival between obese and nonobese LVAD recipients . However, higher rates of hospital readmissions and complications such as AKI , infection , thromboembolism , and PT are often present in the obese cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Our study found that obesity alone was not an independent risk factor for mortality in patients who underwent CF-LVAD implantation [1]. Other groups also have reported that obesity does not seem to be a risk factor for mortality in LVAD patients [2,3].…”
Section: Responsesupporting
confidence: 42%
“…Body mass index was not expected to affect survival, and the statistical differences in creatinine and albumin were not considered clinically significant. 18,19 We observed higher individual vasopressor requirements in the MB group after PSIPW, although the differences were not statistically significant. Although matching based on individual pressor requirements is preferable, the small sample of eligible patients made matching by VIS preferable in this instance.…”
Section: Commentmentioning
confidence: 64%